Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1007/s00223-022-00981-1
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Bone Health Among Indian Older Adults with Obesity, Sarcopenia, and Sarcopenic Obesity

Abstract: Age-related changes in fat and lean mass contribute to bone health, but these associations may be influenced by sex and ethnicity. This study investigated sex-specific associations of obesity and sarcopenia with bone mineral density (BMD) and bone mineral apparent density (BMAD) among Indian older adults. 1057 adults aged ≥ 50 years were included. Dual-energy X-ray absorptiometry (DXA) measured BMD at the hip, spine and whole-body, and BMAD was calculated as BMD/√bone area. Obesity was defined by body fat perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 43 publications
2
6
0
Order By: Relevance
“…Participants in the sarcopenia and sarcopenic obesity groups were older than the rest of the population. This phenomenon has also been found in older Indian adults [ 26 ]. The results also showed that people with sarcopenic obesity had a higher fat mass and visceral fat area than people with sarcopenia but lower fat mass and visceral fat area than those with obesity.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Participants in the sarcopenia and sarcopenic obesity groups were older than the rest of the population. This phenomenon has also been found in older Indian adults [ 26 ]. The results also showed that people with sarcopenic obesity had a higher fat mass and visceral fat area than people with sarcopenia but lower fat mass and visceral fat area than those with obesity.…”
Section: Discussionsupporting
confidence: 64%
“…Similar findings were observed in a 24-year follow-up cohort, which showed that sarcopenic obesity is clinically useful as a predictor of all-cause mortality [ 33 ]. Sarcopenic obesity is also related to cognitive impairment [ 29 ], low bone mineral density [ 26 ], frailty [ 7 ], and metabolic diseases [ 34 ]. A study found that carbohydrate intake could be the best indicator for determining sarcopenic obesity in older adults [ 35 ], and body composition plays an important role in sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we discovered that PSA group participants were more likely to be women than their non‐PSA counterparts. The result is consistent with previous research emphasizing sex differences in sarcopenia, and showing that women were more frequently influenced by sarcopenia than men 26–28 . We noted that the majority of PSA group members had shorter sleep duration and lower bodyweight.…”
Section: Discussionsupporting
confidence: 93%
“…The result is consistent with previous research emphasizing sex differences in sarcopenia, and showing that women were more frequently influenced by sarcopenia than men. [26][27][28] We noted that the majority of PSA group members had shorter sleep duration and lower bodyweight. The present results are in line with that of a prospective study.…”
Section: Discussionmentioning
confidence: 78%